Deskripsi Kemampuan Berpikir Tingkat Tinggi Siswa Kelas XI IPA SMA dalam Menyelesaikan Soal Program Linear ditinjau dari Kecerdasan Adversitas dan Efikasi Diri - Juwita Sari; Nasrullah; Usman Ulbar (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2020)
The aim of this research is to determine the general description of students' adversity quotient and self-efficacy from grade XI IPA and finding out how the description of students higher order thinking skills in solving linear program problems viewed from students’ adversity quotient and self-efficacy. The type of this research is descriptive research with mixed method approach. The subjects of this research were 4 students, those are 1 students has high self-efficacy-climbers, 1 students has low self-efficacy-climbers, 1 students has high self-efficacy-campers, and 1 students has low self-efficacy-campers. The research instrument used consist of ARP questionnaire (Adversity Response Profile), self-efficacy questionnaire, higher order thinking skills test of linear program and interview guidelines. The results of the research showed that: (1) The most of students (70%) had high self-efficacy. (2) The most of students (86,5%) had campers adversity quotient. (3) Students who had high self-efficacy-climbers was able to fulfill three indicators of higher order thinking skills. (4) Students who had low self-efficacy-climbers was able to fulfill two indicators of higher order thinking skills, i.e analyzing and evaluating. (5) Students who had high self-efficacy-campers was able to fulfill two indicators of higher order thinking skills, i.e analyzing and evaluating. (6) Students who had low self-efficacy-campers was not able to fulfill all indicators of higher order thinking skills.